Determination of The Suitable Alternative Dispute Resolution Method For The Construction Industry Players In Malaysia - Chong, Alan Sze Hsyung (2013)
Disputes always occur and are hard to be avoided in the Malaysia construction industry through all these years. Disputes can happen anytime from pre contract until post contract, payment issues, issues regard workmanship, architect instructions are the common factors that lead to dispute in Malaysia construction industry. When dispute occurs different approach of dispute resolution will be adopted to solve or reduce the dispute. There are two main categories of dispute resolution method available for the industry: one is the traditional dispute resolution method(TDR) and the alternative resolution method (ADR). The TDR are methods that are famous and commonly use in the industry all these years, will the ADR is method that are developed to redress the shortage of TDR and provide an alternative means to solve disputes. The objectives of this research are to address the gap of the traditional Dispute Resolution Methods in Malaysia and to identify their problems and to study on different kinds of dispute resolution method and the pros and cons. The main findings of this research determine the suitable types of dispute resolution method the industry players preferred to be adopted, based on the nature and culture of the Malaysia construction industry. The findings will be obtained from analysis based on in-depth interview (qualitative research method) conducted with Malaysia construction experts like the quality surveyors, engineers, and arbitrators/mediators. This is a helpful research which helps to analyse the different ADR METHOD AND TO DETERMINE THE BETTER ADR method used in Malaysia, which help to reduce resolution time, solve dispute as fast as possible, and to spell out which ADR method is suitable for which type.